KAJIAN PENDIDIKAN AGAMA ISLAM DI INDIA - Nuril Khasyi’in (ADIBA : JOURNAL OF EDUCATION, 2021)
The study of Islamic education in India from the results of research that has been carried out using a literature review, the results of the research produced; First, Islam entered India in the 7th century through trade routes. Second, the development of Islam in India can be seen in four stages: first, the period before the Mughal empire (705-1526): second, the reign of the Mughal Empire (1526-1858); third, the period of British rule (1858-1947); the fourth stage, Islam in the secular Indian state (1947 to the present). The development of Islam in India is progressing rapidly and growing after being pioneered by Sayyid Ahmad Khan. And then continued by the leaders and owners of government policies in India, by establishing Islamic schools such as those in New Delhi.